Analysis of Independent Learning Ability and Environmental Literacy of Fifth Grade Elementary School Students on the Development of Learning Outcomes through the Google Form Application - Tinto Wahyu Kisworo (Budapest International Research and Critics University, 2022)
This study aims to analyze the ability of independent learning and environmental literacy of elementary school students in grade 5 (five) on the development of learning outcomes through the google form application. The research method used in this research is descriptive research method, and data collection techniques through interviews and observations, and the google form application. The instruments used are in the form of questionnaires, observation sheets and evaluation questions containing environmental literacy and learning independence which are presented in google forms. The results of the study show that independent learning abilities can be assessed in several ways, namely students are able to answer questions without being appointed when the teacher asks questions about the material contained in the Google Form application, environmental literacy skills can be assessed from several things including students being able to instill a caring attitude. environment by saving electricity.